Physical Activity for Executive Function and Activities of Daily Living in AD Patients: A Systematic Review and Meta-Analysis - Zhu, Lin; Li, Long; Wang, Lin; Jin, Xiaohu; Zhang, Huajiang (Frontiers in Psychology, 2020)
Objectives: The present study aimed to systematically analyze the effects of physical activity on executive function, working memory, cognitive flexibility, and activities of daily living (ADLs) in Alzheimer's disease (AD) patients and to provide a scientific evidence-based exercise prescription. Methods: Both Chinese and English databases (PubMed, Web of Science, the Cochrane Library, EMBASE, VIP Database for Chinese Technical Periodicals, China National Knowledge Infrastructure, and Wanfang) were used as sources of data to search for randomized controlled trials (RCTs) published between January 1980 and December 2019 relating to the effects of physical activity on executive function, working memory, cognitive flexibility, and ADL issues in AD patients. Sixteen eligible RCTs were ultimately included in the meta-analysis. Results: Physical activity had significant benefits on executive function [standard mean difference (SMD) = 0.42, 95% confidence interval (CI) 0.22–0.62, p < 0.05], working memory (SMD = 0.28, 95% CI 0.11–0.45, p < 0.05), cognitive flexibility (SMD = 0.23, 95% CI −0.02 to 0.47, p < 0.01), and ADLs (SMD = 0.68, 95% CI 0.19–1.16, p < 0.05) among AD patients. Subgroup analysis indicated that, for executive function issues, more than 60 min per session for 16 weeks of moderate-to-high-intensity dual-task exercises or multimodal exercise had a greater effect on AD patients. For working memory and cognitive flexibility issues, 60–90 min of moderate-intensity dual-task exercises 1–4 times/week was more effective. For ADL issues, 30–90 min of multimodal exercise at 60–79% of maximal heart rate (MHR) 3–4 times/week had a greater effect on AD patients. Conclusions: Physical activity was found to lead to significant improvements in executive function, working memory, cognitive flexibility, and ADLs in AD patients and can be used as an effective method for clinical exercise intervention in these patients. However, more objective, scientific, and effective RCTs are needed to confirm this conclusion.